Modelo para formação dinâmica de rede de fornecedores em empresas estendidas - Teixeira, Kellyn Crhis (2015)
Supply chains have become an important focus for competitive advantage. The performance of a company increasingly depends on its ability to maintain effective and efficient relationships with its suppliers and customers. The extended enterprise (i.e. composed of several partners) needs to be dynamically formed in order to be agile and adaptable. According to the Digital Manufacturing paradigm, companies have to be able to quickly share and disseminate information regarding planning, designing and manufacturing of products. Additionally, they must be responsive to all technical and business determinants, as well as be assessed and certified for guaranteed performance. The current research intends to present a solution for the dynamic composition of the extended enterprise, formed to take advantage of market opportunities quickly and efficiently. A construction model was developed. This construction model consists of: information model, protocol model and process model. The information model has been defined based on the concepts of Supply Chain Operations Reference model (SCOR®). In this model is defined information for negotiating the participation of candidate companies in the dynamic establishment of a network for responding to a given demand for developing and manufacturing products, in seven steps as follows: request for information; request for qualification; alignment of strategy; request for proposal; request for quotation; compatibility of process; and compatibility of system. The protocol model has been elaborated and inspired in the OSI, this model provides a framework for linking customers and suppliers, indicates a sequence to be followed, in order to selecte companies to become suppliers. The process model has been implemented by means of process modeling according to the BPMN standard and, in turn, implemented as a web-based application that runs the process through its several steps, which uses forms to gather data. An application example in the context of the oil and gas industry is used for demonstrating the solution concept.